Similarity between the 3-minute and traditional measure of critical power in a track cyclist: A casestudy - Richard, N. A.; Koehle, M. S. (Sport Performance & Science Reports, 2020)
Critical power (CP) delineates the boundary between sustainable and unsustainable exercise [1]. Exercise intensity can be broadly categorised into three domains. The severe domain incorporates all work rates above CP. Exercise in this domain will lead to maximal oxygen uptake and/or exhaustion and is limited by a fixed capacity of work (kJ) called the Wprime (W`). Progressive perturbations in metabolic environment such as low [PCr] and pH are characteristics of the severe domain [2]. The work rates between rest and the gas exchange threshold (GET) is called the moderate domain. Exercise inthe moderate domain is well tolerated, swiftly reaches steadystate VO2 and appears limited by muscle glycogen availability and central fatigue. In between the GET and CP, or the moderate and severe domain, is the heavy domain. During exercise in the heavy domain there is a sustained (but not progressive)increase in lactate. Oxygen uptake, despite a slow component (lag), eventually reaches steady-state. Time in the heavy domain may be influenced by muscle glycogen depletion and lowering of [PCr] and pH [2].Track cycling is an Olympic sport and takes place within the banked oval track of a velodrome using a fixed-gear bicycle.With the advancement of portable power meters, the work demands of track cycling can now be quantified. Track cyclingis a relatively "sterile" sport as velodromes are not subject to wind, can be temperature controlled, and the distance andsurface remains constant. A common paradox exists in sports science. Laboratory studies have precision but lack "real-life feel" whereas field-based studies are ecologically valid but are prone to external ariants; track cycling nicely bridges this gap. Critical power is usually measured in the laboratory with cycle ergometry by plotting the inverse of time versus powerwith a series of time trials lasting<20 minutes (TRAD), or by using a single all-out maximal 3 minute test (3MIN). Field studies have examined the determination of CP power using power meters on road bicycles using a series of time trials [3]. However, to our knowledge, CP has yet to be reported on a track bicycle within a covered velodrome. As the TRAD method is relatively time consuming, the rationale for this case study was to conduct a preliminary trial to investigate if measures of CP utilising the 3MIN method would provide similar measures to TRAD, and consequently lead to time savings and less disruption to training programmes.